The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1107/s205698901600428x
|View full text |Cite
|
Sign up to set email alerts
|

Orientational disorder in the one-dimensional coordination polymercatena-poly[[bis(acetylacetonato-κ2O,O′)cobalt(II)]-μ-1,4-diazabicyclo[2.2.2]octane-κ2N1:N4]

Abstract: The one-dimensional coordination polymer, self-assembled from bis­(acetyl­acetonato)cobalt(II) units as metal–complex connectors and 1,4-di­aza­bicyclo­[2.2.2]octane (DABCO) as linkers, can serve for a comparative investigation of the magnetic behaviour of analogous compounds. Space filling more symmetric than atom positions leads to pronounced orientational disorder for the DABCO ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently Morawiec has made a case for using crystallographic bases as an alternative[49], but this is not common at present 2. This is consistent with the definition chosen in MTEX.…”
mentioning
confidence: 99%
“…Recently Morawiec has made a case for using crystallographic bases as an alternative[49], but this is not common at present 2. This is consistent with the definition chosen in MTEX.…”
mentioning
confidence: 99%
“…In addition, several authors have reported the synthesis of extended metal-containing crystal networks through metal–organic frameworks and coordination polymers and, in a smaller proportion, through the use of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%